Pretreatment Systemic Inflammatory Markers, Neutrophil Lymphocyte Ratio, and Platelet Lymphocyte Ratio as a Prognostic Factor in Cervical Cancer: A Retrospective Study - Sarkar, Sabyasachi; Mirza, Behjet; Das, Sumana Maiti; Singh, Dharmendra; Das, Siddhartha (South Asian Journal of Cancer, 2023)
Inflammation has been recognized as a promoter of the neoplastic process initiation and progression. Neutrophilia, lymphocytopenia, and thrombocytosis are hallmarks of inflammatory reaction. The aim of this study is to find the correlation and prognostic value of pretreatment neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), with the recurrence in carcinoma cervix.Data of 208 biopsy-proven cases of squamous cell carcinoma cervix treated with definitive chemoradiotherapy were retrospectively analyzed. Neutrophil, lymphocyte, and platelet count at diagnosis were recorded and NLR and PLR were calculated. The cutoff value of NLR and PLR were calculated using receiver operator characteristics curve analysis. Correlation between locoregional recurrence (LRR) and NLR and PLR is evaluated. Median age of diagnosis is at 50 years. International Federation of Gynecology Obstetrics stage IIB was the most prevalent stage in this study. The NLR and PLR were statistically significantly affecting the LRR. The cutoff value of NLR was 2.45 with a sensitivity of 82.6% and specificity of 77.7%. The cutoff value for PLR was 140.6 with a sensitivity of 85.5% and specificity of 80.6%. On univariate regression analysis stage (p = 0.045), tumor grade (p = 0.001), addiction (p = 0.024), NLR (p < 0.001), and PLR (p < 0.001) were associated with LRR. Multivariate regression analysis showed that NLR (p = 0.005) risk group and PLR (p < 0.001) risk group are independent risk factors associated with LRR.Conclusion High value of NLR and PLR correlate with poor prognosis in squamous cell carcinoma cervix. Hence, these biomarkers may be used as surrogates for tumor prognosis.
Keywords: cervical cancer; prognosis of cancer cervix; neutrophil to lymphocyte; platelet to lymphocyte; ratio